2019
DOI: 10.1063/1.5087266
|View full text |Cite
|
Sign up to set email alerts
|

Modeling realistic multiphase flows using a non-orthogonal multiple-relaxation-time lattice Boltzmann method

Abstract: In this paper, we develop a three-dimensional multiple-relaxation-time lattice Boltzmann method (MRT-LBM) based on a set of nonorthogonal basis vectors. Compared with the classical MRT-LBM based on a set of orthogonal basis vectors, the present non-orthogonal MRT-LBM simplifies the transformation between the discrete velocity space and the moment space and exhibits better portability across different lattices. The proposed method is then extended to multiphase flows at large density ratio with tunable surface … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
62
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 85 publications
(62 citation statements)
references
References 73 publications
0
62
0
Order By: Relevance
“…An efficient nonorthogonal multiple-relaxation-time (MRT) lattice Boltzmann model (LBM) [25] is employed in this study. In the study of Hoang et al [28], it was shown that the 2D simulation delayed the droplet breakup due to ignoring the Laplace pressure caused by the out-droplet plane.…”
Section: A the Lattice Boltzmann Multiphase Modelmentioning
confidence: 99%
See 3 more Smart Citations
“…An efficient nonorthogonal multiple-relaxation-time (MRT) lattice Boltzmann model (LBM) [25] is employed in this study. In the study of Hoang et al [28], it was shown that the 2D simulation delayed the droplet breakup due to ignoring the Laplace pressure caused by the out-droplet plane.…”
Section: A the Lattice Boltzmann Multiphase Modelmentioning
confidence: 99%
“…Multiplication of the explicit form of Eq. (1) by the transformation matrix M leads to the collision equation in the moment space as follows [25,31]:…”
Section: A the Lattice Boltzmann Multiphase Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…In fact, the idea of using a finite set of discrete speeds appeared early in the seminal work [40], where the discrete velocity model was constructed for the Boltzmann equation, and the collision integral was expressed as a nonlinear quadratic term. In the last three decades, the lattice Boltzmann method (LBM), developed from the lattice gas automaton [41,42] and originally based on the discrete simplified Boltzmann equations [25,[43][44][45][46][47][48], has been successfully used as an alternative tool of various partial differential equations for complex systems with a multiphase [49][50][51][52][53][54], multicomponent [55][56][57], mass diffusion [58,59], external force [60], and/or chemical reactions [61,62], etc. In the evolution of the discrete Boltzmann equation, the particle velocity space is dicretized besides the discretization in physical space.…”
Section: Introductionmentioning
confidence: 99%